UNDERSTANDING THE THEORETICAL THOUGHT OF NICCOLÒ MACHIAVELLI IN THE WORK OF SLOBODAN JOVANOVIĆ - Терзић, Предраг (Political Review, 2024)
Slobodan Jovanović divides Niccolò Machiavelli’s life into two distinct periods. The first explores Machiavelli’s life and involvement in governance, while the second focuses on the phase of his life marked by opposition to authority. Two significant events influenced Machiavelli’s life and political activities: the rise of Fra Girolamo Savonarola and the military-political actions of Cesare Borgia in Romagna. In The Prince Machiavelli serves as an intellectual tool recommended by Machiavelli for future rulers. It was written to guide and caution about the advantages and disadvantages of ruling. Decisions and actions of those in power should be based solely on rational grounds. Despite being a republican by inclination, Machiavelli expressed sympathy for the monarch as a military leader while holding negative views on the monarch as a political actor and decision-maker. Jovanović concludes that Machiavelli’s theory reverts to an old understanding of the state as the highest form of human association, abandoning the goals championed by Christianity. By clearly defining the good, though not ideal, ruler, Machiavelli presents his views on various situations associated with state authority. Although initially linked to the political sphere, „Machiavellianism” has come to describe a general approach for those without moral scruples in pursuing their ambitions.
Keywords: Slobodan Jovanović; Niccolò Machiavelli; Machiavellianism; The Prince; Discourses on Livy; Il Principe